PERAN PERMAINAN TRADISIONAL DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI DI RA MADIGONDO TAKERAN MAGETAN - Rulik Endarwati; Ulil Abshor (CV. ADIBA AISHA AMIRA, 2025)
English Character formation in early childhood at RA Madigondo, Takeran, Magetan, is significantly supported by traditional games such as gobak sodor, congklak, and engklek. These games serve not only as entertainment but also as learning tools rich in moral and social values. This study employs a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection instruments. The findings reveal that traditional games foster character values such as honesty, cooperation, responsibility, sportsmanship, and independence. The interactive learning process through games also reflects the dimensions of the Pancasila Student Profile, including critical thinking, collaboration, and global diversity. Moreover, traditional games embody elements of local wisdom that are relevant to building children's identity and cultural character from an early age. Thus, the integration of traditional games into early childhood education proves to be effective in character development and in preserving national culture.